Analisis Informasi Status Keberangkatan Penerbangan Oleh Unit Customer Service PT. Angkasa Pura II Bandar Udara Internasional Husein Sastranegara Bandung - La ode Putra Batara; Gallis Nawang Ginusti (Student Research Journal, 2023)
Process of providing information unit Customer Service Husein Sastranegara International Airport experienced a discrepancy in flight status information between FIDS and AAS at the departure untill passengers were confused because they received different information from each of the information facilities. Purpose this study is determine process of services provided, constraints, and efforts in the process of information services provided. This research was conducted using a qualitative analysis, which tried to describe all conditions that existed, condition of symptoms according to what they were at the time research was conducted. Based on the main problem, namely to analyze the constraints and what efforts are made by information unit Customer Service when there is a difference in scheduled departure flight information. Result of the study show that the flow of service information on status of departure exists in the unit Customer Service Husein Sastranegara International Airport refers to Standard Operating Procedure of PT. Angkasa Pura II 2022 with the aim of providing fast, precise and accurate information services. Constraints on differences in information caused by miscommunication with other unit and less information service staff. Listening detail every Announcement, contacting related units, teamwork and additional personnel are efforts to overcome the obstacles encountered.